2005
DOI: 10.1111/j.0014-3820.2005.tb00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Drive or Behavioral Inhibition in Evolution: Subspecific Diversification in Holarctic Passerines

Abstract: Abstract. Behavioral changes have long been hypothesized to be an important driver of evolutionary diversification in animals, as they expose individuals to new environmental pressures and thus favor evolutionary divergence. There have been few empirical tests of this hypothesis, however, and the mechanisms linking behavioral changes and diversification processes remain controversial. We show here that Holarctic passerines with large brain size relative to body size, a character correlated with a high propensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 75 publications
4
48
0
Order By: Relevance
“…In other words, do species within higher taxonomic units share similar levels of subspecific diversity? In two previous avian studies (Sol et al 2005; Phillimore et al 2007), closely related species differed markedly in subspecies number (75–95% of total variation in subspecies number), whereas differences between genera and subfamily were small (5–25% of total variation). In cuckoos, however, closely related genera differed strikingly in subspecies richness (54.8% of total variation in subspecies richness is at the genus level, with only 38.5% at the species level).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…In other words, do species within higher taxonomic units share similar levels of subspecific diversity? In two previous avian studies (Sol et al 2005; Phillimore et al 2007), closely related species differed markedly in subspecies number (75–95% of total variation in subspecies number), whereas differences between genera and subfamily were small (5–25% of total variation). In cuckoos, however, closely related genera differed strikingly in subspecies richness (54.8% of total variation in subspecies richness is at the genus level, with only 38.5% at the species level).…”
Section: Resultsmentioning
confidence: 73%
“…The direction of contrasts was determined by a dummy variable and we assumed continuous trait evolution, so ancestral trait values were estimated as weighted means of the sister taxa. Despite subspecies being potentially problematic as an estimate of incipient speciation (Zink 2004), they are useful as an index of diversification and as a surrogate measure of genetic fragmentation (Sol et al 2005; Phillimore et al 2007), which may represent an early stage in allopatric speciation (Phillimore & Owens 2006). Although they have traditionally been defined morphologically based on allopatric phenotypic discontinuities, a recent study found that over 35 per cent of avian subspecies showed considerable phylogenetic differentiation at mitochondrial loci (Phillimore & Owens 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence from comparative and experimental studies supports this contention. For example, comparative studies of birds have linked rates of behavioural innovation with range expansion [7][8][9], with rates of evolutionary diversification [10,11] and with dietary and habitat generalism [12,13]. Experimental studies have associated novel problem-solving with fitness components such as mating success and offspring survival [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural innovations -solutions to novel problems, or novel solutions to old problems [1]- are increasingly thought to provide a rich source of phenotypic plasticity and evolutionary change [2][4]. Innovation propensity shows substantial variation across avian taxa and the functional significance of such variation is well documented.…”
Section: Introductionmentioning
confidence: 99%